Code Status Discussions: How to Communicate Effectively with Your Patients About Resuscitation (Out of Print) - Eva Chittenden; Daniel Orjuela; Susannah Clark (Association of American Medical Colleges, 2010)
Abstract Introduction Conducting discussions about code status is a common and important responsibility of clinicians in many specialties. Despite the frequency of these conversations, the teaching that trainees receive in conducting this important communication is highly variable. Traditionally, these skills have been taught through observation and role-play or, more commonly, not taught at all. Direct observation of more experienced providers conducting code status discussions is another important but highly variable educational modality. Role-plays can be useful but are time consuming to arrange and facilitate. In order to address this educational gap, we produced a video tutorial that would allow large numbers of learners to watch simulated patient-clinician interactions, reflect on what they have watched, and hear experts discuss the strengths and weaknesses of these conversations. The target audience is medical students, house staff, and advanced practice nursing students. Methods The tutorial, which takes about an hour to complete, consists of an overview of resuscitation and then a framework for conducting these conversations. The first step is preparation, followed by a discussion of values, a consent process, and finally the summary. The mnemonic device PVCS, for Premature Ventricular ContractionS, helps learners remember this framework. Common pitfalls as well as effective communication techniques are illustrated. Educational modalities include videos of a standardized doctor and/or nurse talking with a patient actor about code status, expert commentary on the videos by nationally renowned palliative care experts, multiple-choice questions with answers, and a customized pocket card that learners print out at the end. Results We are currently conducting a block randomized trial of third-year medical students at the University of California, San Francisco (UCSF), comparing this curriculum to an equivalent written curriculum. Our hypothesis is that a web-based video curriculum will be superior to a written curriculum. The outcome measures are satisfaction with the curriculum, scores on standardized patient checklists, and ability to reflect on conducting these conversations with standardized patients. We have pilot-tested the curriculum extensively at both UCSF and Dartmouth with medical students, advance practice nursing students, and medicine residents. In addition, we have shared the website with other palliative medicine faculty at UCSF, Dartmouth, and Harvard. Discussion The curriculum is useful as an individual tool or as the focus of a small-group session for medical students or residents. Learners find it helpful to be able to discuss the material with peers and faculty. We have also used the curriculum as an introduction to a standardized patient exercise on conducting code status discussions for third-year medical students.